Thermal integration analysis and improved configuration for multiple effect evaporator system based on pinch analysis - Indra Riadi; Zulfan Adi Putra; Heri Cahyono (Reaktor, 2021)
Pinch analysis for a sugar plant production capacity 4000 TCD has been carried out to reduce its energy consumptions. The plant has ten evaporators that can be configured to several multiple effect evaporators. It has been running with five-effect evaporator (quintuple) scheme. To maximize energy utilization within the plant, three multiple effect evaporator schemes were evaluated. They are triple effect evaporator, quadruple effect evaporator, and quintuple effect evaporator as the benchmark. The result shows that the quintuple effect evaporator yields the highest energy efficiency by about 10%. Options to achieve such target is to use low pressure steam only for the first effect and to use steam bleeding from the first effect to heat a tertiary juice heater. With this proposed scenario, sugar dryer, wash water RVF unit and wash water HGF unit no longer need external steam for its operation.